The Association Between Route of Post-menopausal Estrogen Administration and Blood Pressure and Arterial Stiffness in Community-Dwelling Women - Kalenga, Cindy Z.; Hay, Jacqueline L.; Boreskie, Kevin F.; Duhamel, Todd A.; MacRae, Jennifer M.; Metcalfe, Amy; Nerenberg, Kara A.; Robert, Magali; Ahmed, Sofia B. (Frontiers in Cardiovascular Medicine, 2022)
Background Postmenopausal hormone therapy (HT) is associated with increased cardiovascular risk. Although the route of estrogen administration may play a role in mediating risk, previous studies have not controlled for concomitant progestin use. Objective To investigate the association between the route of estrogen therapy (oral or non-oral) HT use, without concomitant progestin, and blood pressure and arterial stiffness in postmenopausal women. Methods Systolic blood pressure [SBP], diastolic blood pressure [DBP]), arterial stiffness (aortic pulse wave velocity [aPWV] and augmentation index at 75 beats per minute [AIx]) were measured using a validated automated brachial cuff-based oscillometric approach (Mobil-O-Graph) in a community-dwelling sample of 328 women. Results Fifty-five participants (16.8%) were ever users (current and past use) of estrogen-only HT (oral [n = 16], transdermal [n = 20], vaginal [n = 19]), and 223 were never HT users (control). Ever use of oral estrogen was associated with increased SBP and DBP (Oral: SBP: 137 ± 4 mmHg, DBP: 79 ± 2 mmHg) compared to use of non-oral estrogen (transdermal: SBP: 118 ± 2 mmHg, DBP: 73 ± 1 mmHg; p < 0.01 & p = 0.012, respectively; vaginal: SBP: 123 ± 2 mmHg DBP: 73 ± 2 mmHg; p = 0.02 & p = 0.01, respectively.) and controls (SBP: 124 ± 1 mmHg, DBP: 74 ± 1 mmHg, p = 0.03, p = 0.02, respectively) after adjustment for covariates. aPWV was higher in oral estrogen ever users (9.9 ± 1 m/s) compared to non-oral estrogen (transdermal: 8.6 ± 0.3 m/s, p < 0.01; vaginal: 8.8 ± 0.7 m/s, p = 0.03) and controls (8.9 ± 0.5 m/s, p = 0.03) but these associations were no longer significant after adjustment for covariates. AIx was higher in oral estrogen (29 ± 2 %) compared to non-oral estrogen (transdermal: 16 ± 2 %; vaginal: 22 ± 1.7 %) but this association was no longer significant after adjustment for covariates (p = 0.92 vs. non-oral; p = 0.74 vs. control). Conclusion Ever use of oral estrogen was associated with increased SBP and DBP compared to non-oral estrogen use and no use. Given the cardiovascular risk associated with both menopause and increased blood pressure, further studies are required exploring the potential benefits of non-oral estrogen in postmenopausal women.